1968
DOI: 10.1016/0013-4694(68)90044-8
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral evoked responses in hypothyroidism

Abstract: An 8-channel Grass Model III electroencephalograph was employed for EEG recording and to provide pre-amplification of signals processed by 2 computers of average transients (CAT). The frequency response of the system, selected for optimal rejection of myogenic potentials, was such that output amplitude was down 40 % and 80% at 50 c/sec and 100 c/sec respectively (see Kooi and Bagchi 1964a). The scalp electrode

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 11 publications
3
11
0
Order By: Relevance
“…We have previously reported that SCRol was shorter in hyperthyroid patients than in control subjects (17). Similar bidirectional abnormalities related to the CNS in hypothyroidism and hyperthyroidism were previously shown for visual, somatosensory, and auditory evoked po¬ tentials (5,6,25). Avramides (6) also demonstrated pro¬ longed latency of visual evoked potential in hypothyroid pa¬ tients.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…We have previously reported that SCRol was shorter in hyperthyroid patients than in control subjects (17). Similar bidirectional abnormalities related to the CNS in hypothyroidism and hyperthyroidism were previously shown for visual, somatosensory, and auditory evoked po¬ tentials (5,6,25). Avramides (6) also demonstrated pro¬ longed latency of visual evoked potential in hypothyroid pa¬ tients.…”
Section: Resultssupporting
confidence: 65%
“…Nishitani and Kool (25) studied cerebral evoked responses to light in patients with hypothyroidism. They found that average latencies of all waves examined were longer for the patients (25). The mechanism of this thyroid hormone ef¬ fect on cerebral function remains enigmatic.…”
Section: Resultsmentioning
confidence: 95%
“…Complementary to a reduction in CFF, flash evoked potentials showed increased latencies and reduced amplitudes in hypothyroid patients 6 weeks after thyroidectomy which were reversed after 8 weeks of treatment (16). Consistently, visual evoked potentials using chequerboard reversal patterns showed reversible increases in latencies and reductions in amplitudes in hypothyroidism (17, 19-21, 23, 24, 71-73).…”
Section: Speed Of Processing Of Visual Signalsmentioning
confidence: 58%
“…However, a decrease in sodium current density could as well explain the decreases in peripheral conduction velocities and increases in latencies of evoked potentials found in hypothyroidism (16)(17)(18)(19)(20)(21)(22)(23)(24) and reversely the increased amplitudes in hyperthyroidism (177,178). Since there seems to be an optimal density of sodium channels that ensures maximal neuronal conduction velocity (179), beyond which no further increase or even a slowing of conduction velocity occurs, an upregulation of sodium currents by thyroid hormone could also explain the inconsistent findings concerning latencies of evoked visual potentials in hyperthyroidism, where some authors found decreases in latencies (180) or even increases with increases in thyroid hormone (21,71,177,178).…”
Section: Changes In Conduction Velocity Action Potential Waveform Anmentioning
confidence: 99%
See 1 more Smart Citation